EVALUASI PERENCANAAN PEMBANGUNAN DESA BERBASIS IDM DAN SDGs DESA: STUDI KASUS RKPDes DESA RESAM LAPIS - Yuri Marisa; Taryono Taryono; Wellyn Cesharina Meylan; Syakirah Athiyyah Fitri; Melani Noviantori Ramadhan; Renata Deliana; Naila Septa Ridhoni (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to evaluate the alignment of the 2025 Village Government Work Plan (RKPDes) for Resam Lapis Village, Bengkalis Regency, with the Village Development Index (IDM) data and the Village Sustainable Development Goals (SDGs). The method used is an evaluative study employing a qualitative descriptive approach through document analysis and the analysis of secondary data from the official website of the Ministry of Villages, Development of Disadvantaged Regions, and Transmigration. The results of the study indicate that although Resam Lapis Village has achieved the status of an Independent Village with an IDM score of 0.8929, the formulation of the RKPDes remains dominated by a routine administrative approach characterized by copy-paste practices without strategically referencing IDM data and Village SDGs. Of the 18 Village SDGs, only 33% are fully accommodated, while 28% are not accommodated at all, particularly in the environmental aspects (Goals 12 and 13 with a score of 0.00). Budget allocation remains focused on physical infrastructure, while economic empowerment and social resilience receive insufficient attention. This study recommends integrating IDM and Village SDG data as a basis for planning, strengthening the capacity of village officials, and reorienting the budget toward more productive and sustainable development.